Development Strategies of Tourism Object of Sowan beach in Bancar Subdistrict, Tuban Regency - Ahadina Dwi Insani (Program Pendidikan Vokasi Universitas Brawijaya, 2013)
The determination of regional autonomy based on the decree No. 22 year 1999 has become the gateway for regional government to manage and develop the regional potential to create area development and growth comprehensively and harmoniously. One of regional sectors which can be developed is tourism. Tourism sector in Tuban regency is potential to attract tourists’ visits. For instance, natural potential, local culture, and history which can be developed further by taking advantage of Tuban location as the gateway of East Java province through Pantai Utara ways. One of well-known tourism objects in Tuban regency is Sowan beach. The aims of this study is to evaluate strengths and weaknesses in planning area which can support tourism development at Sowan beach that include basic condition, facilities, tourists, and managers. The existing strengths of the potentials are then used to determine possibilities of tourism product development at Sowan beach based on the existing policies. Strategies of tourism development at Sowan beach are then determined which cover non-physical development such as tourism linkage system, physical development such as room design, and facilities development.